Ectopic ACTH Production in Carcinoma of the Lung - Gewirtz, George (1974)
Immunoreactive ACTH was found in almost all tissue extracts of lung carcinoma from patients without clinical evidence of Cushing's syndrome; i.e. 14 of 15 primary tumors, nine of nine metastatic lymph nodes, and four of four metastatic liver nodules contained immunoreactive ACTH. The incidence of ACTH in extracts of other tumor types was much lower. Comparable normal tissues contained no detectable ACTH. Immunoreactive growth hormone, parathyroid hormone, or gastrin was not found in the same carcinoma tissue. The predominant form of ACTH in the tumor extracts was big ACTH. In pituitary extracts little ACTH predominated. 53% of 83 patients with lung carcinoma had afternoon plasma ACTH levels greater than 150 pg/ml; more than 90% of plasmas containing less than 150 pg/ml were obtained from patients who had received radiation therapy or chemotherapy. 31% of 45 patients with chronic obstructive pulmonary disease (COPD), 28% of 25 patients with other severe lung disease, and 6% of 33 controls had elevated values. Big ACTH predominated in the plasma of patients with lung carcinoma or COPD having elevated ACTH levels. Tissue from the lung of a smoking dog with atypical histologic changes contained immunoreactive ACTH, almost exclusively in the big form, while tissue from another smoking dog that was histologically normal contained no ACTH. Thus ACTH may be present even in precancerous lung lesions. These studies suggest that serial plasma ACTH levels may be of value in screening for, and/or management of, patients with carcinoma of the lung.